Diabetes-Induced Reactive Oxygen Species: Mechanism of Their Generation and Role in Renal Injury - Selim Fakhruddin; Wael Alanazi; Keith E. Jackson (Journal of Diabetes Research)
Diabetes induces the onset and progression of renal injury through causing hemodynamic dysregulation along with abnormal morphological and functional nephron changes. The most important event that precedes renal injury is an increase in permeability of plasma proteins such as albumin through a damaged glomerular filtration barrier resulting in excessive urinary albumin excretion (UAE). Moreover, once enhanced UAE begins, it may advance renal injury from progression of abnormal renal hemodynamics, increased glomerular basement membrane (GBM) thickness, mesangial expansion, extracellular matrix accumulation, and glomerulosclerosis to eventual end-stage renal damage. Interestingly, all these pathological changes are predominantly driven by diabetes-induced reactive oxygen species (ROS) and abnormal downstream signaling molecules. In diabetic kidney, NADPH oxidase (enzymatic) and mitochondrial electron transport chain (nonenzymatic) are the prominent sources of ROS, which are believed to cause the onset of albuminuria followed by progression to renal damage through podocyte depletion. Chronic hyperglycemia and consequent ROS production can trigger abnormal signaling pathways involving diverse signaling mediators such as transcription factors, inflammatory cytokines, chemokines, and vasoactive substances. Persistently, increased expression and activation of these signaling molecules contribute to the irreversible functional and structural changes in the kidney resulting in critically decreased glomerular filtration rate leading to eventual renal failure.